Asymmetric Synthesis of Chiral γ‐ and δ‐Amino Esters Using Trichlorosilane Activated with a Lewis Base Catalyst. Issue 20 (27th May 2020) - Hasdemir, Belma; Yaşa, Hasniye; Yıldız, Tülay; Küçük, Hatice Başpınar; Onar, Hülya Çelik
Abstract: Novel chiral γ‐ and δ‐ amino esters 2 a –k were synthesized by enantioselective reduction of N ‐aryl γ‐ and δ‐imino esters with aryl, substituted aryl, and heteroaryl groups 1 a –k using trichlorosilane activated with optically active N ‐pivaloyl L ‐proline I in high yields (50%–98%) with enantioselectivities (10%–84% enantiomeric excess). The structures of the chiral amino esters 2 a –k were clarified by infrared, nuclear magnetic resonance ( 1 H and 13 C) and gas chromatography‐mass spectrometry. The enantiomeric excess of these compounds were identified by chiral high‐performance liquid chromatography using a Chiralpak AD−H column. The highest ee of 84% and highest yield of 98% were found for 2 d . Abstract : The different structure new chiral amino esters 2 a –k were synthesized by the asymmetric reduction of their corresponding imino esters 1 a –k. The asymmetric reduction was achieved by trichlorosilane activated chiral N ‐pivaloyl L ‐proline I. The highest ee of 84% and highest yield of 98% were found for 2 d . These compounds can be extensively used as chiral starting materials, auxiliaries, and a chiral catalyst in organic synthesis.